Paper Tube Emergency Shelters - Shigeru Ban (Oz, 2006)
In the 1990s, ethnic violence between the Hutu and Tutsi peoples broke out in Rwanda. As a result, more than two million people became refugees. The tragedy was raised in the public consciousness by constant media attention and even became the subject of the film Hotel Rwanda.